Antiplasmodial activity against resistant strains, toxicity and effect on mouse liver enzymes of extracts of Terminalia species found in Southwest Cameroon - Moses Njutain Ngemenya; Grace Ntube Abwenzoh; Denis Zofou; Thierry Roland Kang; James Ajeck Mbah (Shahrekord University of Medical Sciences, 2021)
Introduction: Terminalia species have the potential to be exploited in phytomedicine based on their several pharmacological properties including antiplasmodial activity. However, there is need for more data on their antiplasmodial activity and toxicity. This study evaluated the antiplasmodial activities of Terminalia catappa and Terminalia superba found in the coastal area of Cameroon on resistant strains of Plasmodium falciparum not previously tested, and their toxicity. Methods: Three leaf extracts of each plant prepared separately using three organic solvents were screened in vitro on 3 strains of P. falciparum: chloroquine-sensitive 3D7, chloroquine-resistant Dd2 and multi-drug resistant W2mef using the parasite growth inhibition assay. Antiplasmodial activity was assessed using fluorescence microscopy and the parasite lactate dehydrogenase assay. Cytotoxicity of active extracts was assessed on LLC-MK2 monkey kidney epithelial cells and acute toxicity including effect on some liver enzymes in BALB/c mice. Results: The methanol extracts of both plants showed the highest antiplasmodial activity (IC50 between 5.03-9.76 μg/mL) on the three parasite strains. The methanol extracts showed high selectivity for parasites with selectivity index values ranging from 40 to 80 indicating very low risk of toxicity. There was no mortality or adverse effect and no significant effect on the liver enzymes, alanine aminotransferase (P = 0.506) and aspartate aminotransferase (P = 0.243). Conclusion: The antiplasmodial activity, high selectivity and no adverse effects for T. catappa and T. superba demonstrate the potential for use of these plants in traditional treatment of malaria, further development into a phytomedicine against malaria and as source of new antimalarial lead.